Analysis of the Customer Satisfaction of Black Market’s Chinese Smartphone - Liana Mangifera; Febrianur Ibnu Fitroh Sukono Putra (Journal of Management and Entrepreneurship Research, 2021)
Objective: This research aims to analyse the factors that influence customer satisfaction of black market’s Chinese smartphone. Research Design & Methods: The research uses quantitative approach to analyse the sample of 250 buyers of black market’s Chinese smartphone across Solo Raya. The sampling technique is purposive sampling through questionnaires with a Likert scale. The analytical technique is multiple regression. Findings: The findings showed that 1) black market has a significant direct effect on customer satisfaction, 2) price has a significant direct effect on customer satisfaction, 3) product quality has a significant direct effect on customer satisfaction. Implications & Recommendations: This research has practical implications for the marketing policies implemented by Chinese smartphone companies to increase customer awareness and product distribution policies to support increased sales at official stores and fight illegal trade in Chinese smartphone products. The social impact of the research is to contribute to changes in people's behavior in buying Chinese smartphones where there needs to be aware that the black market is an illegal store to buy products if people want to buy Chinese smartphones, then the right thing is at official stores or outlets that are already working—same with the company. Contribution & Value Added: This research provides added value to evaluating distribution policies implemented by Chinese smartphone companies, which are considered less able to compete with the black market. So to increase market share at official stores, Chinese smartphone companies must be more severe in managing the distribution of product sales so that industrial competition can run properly.